Screening of cognitive impairment by general internists using two simple instruments - Alessandro Ferrari Jacinto; Sonia Maria Dozzi Brucki; Claudia Sellitto Porto; Milton de Arruda Martins; Ricardo Nitrini (Dementia & Neuropsychologia)
ABSTRACT General internists (GIs) tend to overlook cognitive impairment in the elderly. Lack of time to diagnose and/or poor knowledge on how to use screening instruments may be the reasons for this shortcoming. Objectives: To verify the efficacy of simple instruments in the screening of cognitive impairment in elders. Methods: In a previous study, 248 patients aged ≥65 that had been assisted by GIs within outpatient services of a public university hospital in São Paulo, Brazil, were evaluated. The Mini-Mental State Examination and/or the Informant Questionnaire on Cognitive Decline in the Elderly (short-IQCODE) were employed to classify patients into probable cognitively impaired cases or otherwise. Other tests and questionnaires were also applied, but were not used to perform this classification. After full assessment and consensus meetings, cases were classified into dementia, cognitively impaired not demented, and without cognitive impairment. In this study, the sensitivity and specificity of the combined use of the category fluency test (CFT) and the Functional Activities Questionnaire (FAQ) was evaluated as if used as screening instruments for the whole sample. Results: The combined use of the CFT and/or FAQ showed sensitivity of 88.3% and specificity of 76.5% in the screening of cognitive impairment for the whole sample. Conclusions: Two simple and easy-to-apply instruments showed high sensitivity and reasonable specificity, and are probably useful for the screening of cognitive impairment in the elderly in outpatient services.